Wagner's The ring of the Nibelung - Wagner, Richard, 1813-1883 (Opera Journeys, 2002)
Opera classics library explores the inner soul of Wagner's colossus of music theater. All of the Ring's mysteries are unlocked, and its immensity and complexity are analyzed and made coherent for the newcomer as well as for the seasoned enthusiast.
Keywords: Wagner, Richard, -- 1813-1883. -- Ring des Nibelungen.; Ring des Nibelungen (Wagner, Richard); Operas -- Librettos.; Opéras -- Livrets.; MUSIC -- Genres & Styles -- Opera.; Operas -- Librettos